Assessment of the Structural Capacity and Strengthening./Proposals of an Existing Wastewater Treatment Facility. - Kardala Maria; Kotronis Panagiotis (2017)
Introduction, Advantages and Disadvantages of Reinforced Concrete, Basic Elements for the Reinforcement Concrete, Seismic Assessment and Retrofitting of Structures, Assessment Procedure, Non-Destructive Testing Methods of Materials, Destructive Testing Methods of Materials, Analysis Based on Core Samples, Petrographic Chemical Physical Analysis, Rebound Hammer Test. Core Drilling, Diamond Core Driller / Cutter Machine, Effects on the Surface of Concrete, Corrosion, Cracking, Repair of Reinforced Concrete Elements, Selected Concrete Strengthening Methods, FRP Method, Calculation of Loads Distribution, Initial SAP Model and Application of Loads, Calculation of Mass of the Structure, Moments Summary Tables for Effects of Loads, Calculation for the FRP Strengthening Method for Beams, Calculation for the RC Jacketing Strengthening Form of Columns, Estimation of Cost, References, Appendix.